InDels in an intronic region of gene Ccsmd04 coding for dormancy/auxin-associated protein control sterility mosaic disease resistance in pigeonpea - Rangari, Sagar Krushnaji; Dube, Namita; Sharma, Vinay; Gangurde, Sunil S.; Sharma, Mamta; Gangashetty, Prakash I.; Saxena, Rachit K.; Moghiya, Abhinav; Sharma, Vinay K.; Bhutia, Karma L.; Kant, Ravi; Thudi, Mahendar; et al. (Elsevier, 2025)
Sterility mosaic disease (SMD) presents a significant challenge to pigeonpea cultivation in the Indian subcontinent, potentially leading to total crop failure. The development of diagnostic molecular markers for SMD resistance can aid in developing SMD-resistant varieties. In this context, a QTL-seq approach identified genomic regions associated with SMD resistance using a recombinant inbred line population generated from ICP8863 × ICPL87119. In total, 6105 high-confidence variants were identified in the genomic region, smdCc04 based on the ΔSNP index. A genomic region smdCc04 on chromosome Cc04 spans 3.2 Mb (9.3–12.5 Mb) comprises 5 missense variants and 9 Indels. A total of 211 candidate genes were identified from this region. 1 bp insertion, 21 bp insertion, 9 bp deletion, and 3 bp insertion at different intronic positions in 22 susceptible genotypes leads to downregulation of Dormancy/auxin associated protein (Ccsmd04 gene) resulting in loss of signaling in disease resistance pathways. The identified sites recognize four important disease and plant growth related transcription factors. A total of 4 InDels and 8 SNPs were validated from smdCc04 genomic region using whole genome re-sequencing data and kompititive allele specific polymerase chain reaction (KASP) genotyping in resistant and susceptible pigeonpea genotypes. Gene-based markers snpCC00149 and snpCC00150 present in the genomic region smdCc04 can be used in pigeonpea breeding programs for developing SMD resistant varieties.